Chorebus (Phaenolexis) brevivalvis TOBIAS 1998 ... - Papp, J. (Zenodo, 2007)
Chorebus (Phaenolexis) brevivalvis TOBIAS, 1998 – 1 ♀: KU 22. 2 ♀: KU 27. – Described from Asiatic Russia (Primorski Krai, Sakhalin) on the basis of two females. New to the fauna of Korea. – Antenna with 32 antennomeres (1 ♀). First tergite three times as long as broad behind. Wings subfumous. ... : Published as part of Papp, J., 2007, Braconidae (Hymenoptera) From Korea Xxii. Subfamily Alysiinae, pp. 1-38 in Acta Zoologica Academiae Scientiarum Hungaricae 53 (1) on page 8, DOI: 10.5281/zenodo.5731826 ...